Micro- and meso-structural changes on electrically cured ultra-high performance fiber-reinforced concrete with dispersed carbon nanotubes. (November 2020) - Jung, Myungjun; Park, Ji-seul; Hong, Sung-Gul; Moon, Juhyuk
Abstract: This study investigated the potential application of electrical curing method on ultra-high performance fiber-reinforced concrete (UHPFRC) by incorporating carbon nanotubes (CNTs) and resulting structural changes in micro- and meso-scale. The addition of CNTs significantly decreased the electrical resistance of the UHPFRC, and the temperature inside the UHPFRC was able to increase to 90 °C under low voltage by the Joule effect. This enabled electrical curing, which can produce a similar effect to steam curing but in a much more energetically efficient way. The added CNTs slightly hindered the hydration reaction of the UHPFRC, but it modified the formation of C-(A)-S-H to be denser, stiffer, and more complex which have been evidenced by observed partial cross-linking in the C-(A)-S-H and the higher fractal dimension of solid system. The results of this study are promising for using UHPFRC in on-site field condition and extending the application of CNTs in structural materials. Graphical abstract: Unlabelled Image